2014
DOI: 10.1371/journal.pone.0101392
|View full text |Cite
|
Sign up to set email alerts
|

FBXO7 Y52C Polymorphism as a Potential Protective Factor in Parkinson's Disease

Abstract: Mutations in the F-box only protein 7 gene (FBXO7), the substrate-specifying subunit of SCF E3 ubiquitin ligase complex, cause Parkinson's disease (PD)-15 (PARK15). To identify new variants, we sequenced FBXO7 cDNA in 80 Taiwanese early onset PD patients (age at onset ≤50) and only two known variants, Y52C (c.155A>G) and M115I (c.345G>A), were found. To assess the association of Y52C and M115I with the risk of PD, we conducted a case–control study in a cohort of PD and ethnically matched controls. There was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…-Reduced capacity to recruit Parkin to mitochondria. [10,11,13,14,27,45,46] Other SNPs in FBXO7 have also recently been identified in relation to idiopathic PD; an allele encoding for p.Y52C is associated with decreased risk of disease in Chinese and Taiwanese patients [17], whereas a non-coding IVS-329C>T variant is moderately associated with increased risk [16]. Other GWAS studies have identified SNPs in FBXO7 as being relevant for measurable erythroid parameters, including one that causes a coding substitution (p.M115I) [18].…”
Section: R378gmentioning
confidence: 99%
See 1 more Smart Citation
“…-Reduced capacity to recruit Parkin to mitochondria. [10,11,13,14,27,45,46] Other SNPs in FBXO7 have also recently been identified in relation to idiopathic PD; an allele encoding for p.Y52C is associated with decreased risk of disease in Chinese and Taiwanese patients [17], whereas a non-coding IVS-329C>T variant is moderately associated with increased risk [16]. Other GWAS studies have identified SNPs in FBXO7 as being relevant for measurable erythroid parameters, including one that causes a coding substitution (p.M115I) [18].…”
Section: R378gmentioning
confidence: 99%
“…Other GWAS studies have identified SNPs in FBXO7 as being relevant for measurable erythroid parameters, including one that causes a coding substitution (p.M115I) [18]. However, no significant association between this SNP and PD has been found [17,19]. Mapping these pathogenic mutations and associated SNPs to different FBXO7 exons indicates that many of its functional protein domains may be affected to cause pathology; however, most of these alterations cluster in or around the N-terminal ubiquitin-like (Ubl) domain, or the C terminal F-box domain (FBD) and proline rich region (PRR) ( Figure 1A).…”
Section: R378gmentioning
confidence: 99%
“…The FBXO7 gene also displays various single-nucleotide polymorphisms (SNPs) and a recent study examined the cosegregation of PD and SNPs that generate the missense mutations Y52C and M115I. The results revealed significantly fewer individuals with PD that carry the G allele of the Y52C SNP (Chen et al 2014), suggesting a protective genotype. While this is an intriguing finding, the minor allelic frequency of the G allele in the control group is very low, which requires further validation with larger cohorts.…”
Section: Fbxo7 Gene Protein and Mutationsmentioning
confidence: 99%
“…In 2008, a point mutation in FBXO7 was linked to a familial form of PD , presenting an early‐onset Parkinsonism with pyramidal signs. Subsequently additional mutations have been found in early‐onset cases and in patients with sporadic PD . PARK15 PD patients are levodopa‐responsive, but rapidly develop side effects, such as dyskinesia .…”
Section: Introductionmentioning
confidence: 99%